2020
DOI: 10.1101/2020.10.20.346940
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermosensitivity of the voltage-dependent activation of calcium homeostasis modulator 1 (calhm1) ion channel

Abstract: Calcium homeostasis modulator 1 (calhm1) proteins form an outwardly rectifying nonselective ion channel having exceedingly slow kinetics and low sensitivity to voltage that is shifted by lowering extracellular Ca2+ ([Ca2+]e). Here we found that physiological temperature dramatically facilitates the voltage-dependent activation of the calhm1 current (Icalhm1); increased amplitude (Q10, 7-15) and fastened speed of activation. Also, the leftward shift of the half-activation voltage (V1/2) was similary observed in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
(45 reference statements)
1
1
0
3
Order By: Relevance
“…2A, middle panel). We recently report-ed on the thermosensitivity of CALHM1 (Jeon et al, 2021) and confirmed the significant facilitation of CALHM1 activation at physiological temperature (37°C, Fig. 2A, right panel).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…2A, middle panel). We recently report-ed on the thermosensitivity of CALHM1 (Jeon et al, 2021) and confirmed the significant facilitation of CALHM1 activation at physiological temperature (37°C, Fig. 2A, right panel).…”
Section: Resultssupporting
confidence: 73%
“…In whole-cell patch clamp studies, CALHM1-expressing cells showed slowly activating outward currents under strong depolarized conditions, and the voltage-dependence was shifted to the left by lowering the extracellular Ca 2+ concen-tration ([Ca 2+ ] e ) (Ma et al, 2012). We have recently reported that both voltage dependence and activation speed were markedly potentiated by raising the temperature to physiological ranges (Jeon et al, 2021). Also, CALHM1 current activation shows tendency of sensitization by repetitive stimuli as like the voltage-dependent activation of Anoctamin 6/ TMEM16F (Roh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Outro estudo usando um serviço de mensagens também relata que maiores pontuações na BBPS e taxas de PI adequado foram obtidas pelo grupo de intervenção (15) . Em dois estudos os pacientes no grupo de intervenção receberam vídeos educacionais antes do procedimento e resultados similares foram obtidos (13,30) .…”
Section: Discussionunclassified
“…O GI no nosso estudo apresentou um TDP bem próximo do padrão mínimo. A análise de estudos em que os pacientes receberam educação aprimorada mostrou que as taxas de DA e DP foram significativamente mais altas nos grupos de intervenção de alguns estudos (12,(15)(16)(17)30) , enquanto alguns dos estudos não reportaram diferenças significativas (11,(13)(14) .…”
Section: Discussionunclassified
See 1 more Smart Citation